(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim. Molecular docking experiments employing a molecular docking server will be used to find novel drugs against mutant structures of the MAPT protein linked to Alzheimer's disease. Materials and Methods. In this study, we used SWISS-Attach to dock phytochemicals Curcumin and Resveratrol with mutant structures of MAPT protein V287I mutation, which were predicted to have destabilizing effects on the MAPT protein by Dynamut.Alzheimer’s disease, EOAD, PSEN2, Mutant structures, Novel compounds, Molecular Docking, SWISS-DOCK. Sample size chosen for this study was 1 mutation for the MAPT gene. Results. The binding energies of the docked molecules were investigated. Conclusion. Using the molecular docking online tool that we employed in our investigation, we performed molecular docking of mutant MAPT protein structures with putative phytochemicals. These docked chemicals could help with medication development investigations and uncover a possible AD treatment.